Principals’ Leadership Practices and Instructional Effectiveness in Senior Secondary Schools in Ilorin South Local Government, Kwara State, Nigeria (Kwasu International Journal of Educational Management and Leadership, 2026)
This study investigated the principals’ leadership practices and instructional effectiveness in senior secondary schools in Ilorin South Local Government, Kwara State. The study was driven by the persistent concern over declining academic performance and the central role of school leadership in improving instructional quality. A descriptive survey design of correlational types was adopted for the study. The population comprised of 59 senior secondary schools and 20 schools were sampled purposively to ensure more detailed and maintaining quality of data analysis. Whereby, five teachers each were selected as samples for the study totaling 100 respondents. Data was collected and administered through a structured questionnaire titled Principals’ Leadership Practices and Instructional Effectiveness Questionnaire (PLPIEQ). The instrument, comprising 30 items, demonstrated a high reliability coefficient of 0.95. Descriptive statistics of mean and standard deviation were used to answer the research questions on the prevalence of leadership practices among principals while inferential statistics was used to test the hypothesis using the Pearson Product-Moment Correlation Coefficient (PPMC) to examine the relationship between leadership practices and instructional effectiveness. The results showed that there is a significant relationship between principals’ leadership practices and instructional effectiveness in senior secondary school in Ilorin-south, Kwara state (r = 0.68, p= 0.000 @ 0.05 level of significance). The findings revealed that principals’ leadership practices had a significant relationship with instructional effectiveness in senior secondary schools in Ilorin South Local Government of Kwara State. In conclusion, principals who adopt strong leadership practices positively influence teaching quality, teacher morale, and overall student academic performance which remains critical for driving better instructional outcomes in schools. It was recommended that Principals should prioritize regular professional development workshops for teachers, ensuring they remain updated with current pedagogical methods to boost instructional effectiveness in senior secondary schools, Ilorin south Local Government, Kwara state.